TEACHERS' SPIRITUAL MENTORING STRATEGY IN IMPROVING STUDENTS' LEARNING MOTIVATION AT MADRASAH ALIYAH - Wilda Faridatul Azman; Kustiana Arisanti; Ummi Lailia Magfiroh (Journal Analytica Islamica, 2026)
This study examines the implementation of spiritual mentoring conducted by teachers in enhancing students’ learning motivation within the madrasah environment. Learning motivation remains a significant issue influenced not only by academic factors but also by students’ psychological conditions and social environments. This research employed a qualitative approach using a case study design conducted at MA Mirqotul Ulum Liprak Kulon Banyuanyar. The research subjects consisted of teachers and students involved in spiritual mentoring activities who were selected purposively based on their direct participation in the mentoring process. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that spiritual mentoring was implemented through several interconnected strategies, including group mentoring, individual approaches, teacher role modeling, and the habituation of religious practices. These strategies were integrated into both classroom learning activities and extracurricular programs. The study found that students demonstrated increased engagement in learning, stronger discipline, and greater responsibility toward academic tasks. Learning motivation developed alongside students’ growing awareness of learning as part of their personal values and spiritual responsibilities. Supporting factors included a conducive school environment and positive teacher–student relationships, while the main challenges were limited time allocation and differences in students’ backgrounds. The findings indicate that the integration of spiritual approaches in educational practices contributes positively to the development of students’ internal learning motivation.